The Influence of using Suggestopedia Method Toward Studentsâ€™ Vocabulary Mastery at Eight Grade of the Second Semester in SMPN 06 Metro in Academic Year 2016/2017 - Baihaqi, Yasmika; Rutiningsih, Maya (ENGLISH FRANCA : Academic Journal of English Language and Education, 2018)
English is the foreign language that we have to learn it early. Not just our country, it is very important because all of the countries use it to communicate each other. It proves that language is necessary for people to interact with other people. There are some problem formulations in this research those are â€œIs there any positive and significant influence of using suggestopedia method toward studentsâ€™ vocabulary mastery at eight grade of the second semester in SMPN 06 Metro academic year 2016/2017?â€ The objective of this research is to know influence of using suggestopedia method toward studentsâ€™ vocabulary mastery. The kind of this research is quasi experimental design. The research was conducted at eight grade of the second semester in SMPN 06 Metro academic year 2016/2017. The researcher took two classes at eighth grade as the sample, 29 as the experiment class and 29 were included as control class which were taken by using cluster random sampling. In collecting the data, the researcher used pre-test and post-test. In analyzing the data, the researcher used parametric ttest formula. After analyzing the result of data by using parametric formula, the researcher gets the result of tratio is 3,009 and ttable 2,66. It means that tratio > ttable, Ha is accepted if tratio > ttable. So, there is significant influence of using suggestopedia method toward studentsâ€™ vocabulary mastery at eight grade of the second semester in SMPN 06 Metro academic year 2016/2017.